Proliferatif vitreoretinopati - Şentürk, Fevzi; Aras, Cengiz (My University, 2019)
Proliferatif vitreoretinopati (PVR) ektsrasellüler matriks proteinleri ve çeşitli hücrelerden oluşan fibro-sellüler membran formasyonu ile karakterize bir durumdur. PVR basit retina üzerinde kırışıklık yapan basit membranlardan komplike tünel formasyonuna neden olan rijit total retina dekolmanına kadar geniş bir yelpazede karşımıza çıkabilir. PVR yırtıklı retina dekolmanı cerrahisinde başarısızlığın en önemli nedenidir. PVR’de görünen istenmeyen membranların oluşumunda çeşitli sitokinler, büyüme faktörleri ve çeşitli hücreler yer almaktadır. PVR’de oluşan bu intrensek önemli hücresel olayların anlaşılması tedavi ajanları geliştirilmesinin temelini oluşturmaktadır. Biz bu derlemede PVR gelişiminde rol alan hücresel/moleküler olayları, yeni tedavi stratejilerini ve güncel cerrahi eğilimleri özetlemeyi amaçladık.

Proliferative vitreoretinopathy (PVR) characterized with formation of fibro-cellular epiretinal membranes composed of extracellular matrix proteins and cells. PVR presents with a spectrum of severity ranging from subtle retinal wrinkling to funnel type total rigid retinal detachment. PVR is the major cause of failure in surgery to rhegmatogenous retinal detachment. There exists play between various cytokines/growth factors, and the different cell types that drive the undesirable formation of periretinal membranes. This fundamental understanding is aiding in identifying different adjunct agents that can block the cellular events intrinsic to PVR. In this review, we describe the current understanding on the pathogenesis and discuss how the fundamental understanding of the cellular/molecular events is instrumental in developing the novel treatment strategies and current surgical trends that are also mentioned.
Proliferative vitreoretinopathy
Keywords: Proliferatif vitreoretinopati (PVR); Ektsrasellüler Matriks Proteinleri; Hücre; Proliferative Vitreoretinopathy (PVR); Characterized With Formation; Cell